2016
DOI: 10.1002/chem.201505126
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Protein‐Induced Absorption Shifts of Retinal in Engineered Rhodopsin Mimics

Abstract: Rational design of light-capturing properties requires understanding the molecular and electronic structure of chromophoresi nt heir native chemical or biological environment. We employ here large-scale quantumc hemical calculations to study the light-capturing properties of retinal in recently designedh uman cellular retinol binding protein II (hCRBPII) variants (Wang et al. Science, 2012, 338,1 340-1343. Our calculations show that these proteins absorb across al arge part of the visible spectrum by combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…To overcome these limitations, recent theoretical studies have extended the quantum treatment to larger regions and suggested that at least one shell of amino acids in proximity of the RPSB chromophore participates in the photo-induced process. 20,24 These findings are qualitatively in line with earlier studies [26][27][28] on prototypical opsins by Elstner and coworkers, who found the environment to electrostatically respond to the photoexcitation of the chromophore when relaxed in a state-specific manner using either a quantum-in-quantum partition or through polarizable force fields. In all these cases, the observed effects were classified as "polarization" but is the polarization captured by a responsive (quantum or classical) treatment of the environment the same one re-covered in the quantum calculation of a large photoexcited region?…”
Section: Introductionsupporting
confidence: 90%
“…To overcome these limitations, recent theoretical studies have extended the quantum treatment to larger regions and suggested that at least one shell of amino acids in proximity of the RPSB chromophore participates in the photo-induced process. 20,24 These findings are qualitatively in line with earlier studies [26][27][28] on prototypical opsins by Elstner and coworkers, who found the environment to electrostatically respond to the photoexcitation of the chromophore when relaxed in a state-specific manner using either a quantum-in-quantum partition or through polarizable force fields. In all these cases, the observed effects were classified as "polarization" but is the polarization captured by a responsive (quantum or classical) treatment of the environment the same one re-covered in the quantum calculation of a large photoexcited region?…”
Section: Introductionsupporting
confidence: 90%
“…The most extended color tuning study on a retinal protein was carried on the human cellular retinol binding protein II (hCRBPII) that was converted into a retinal binder 36 . Mutagenesis of the retinal-binding pocket lead to a protein with absorption at 644 nm 37 , 38 , a strong bathochromic shift that depends on the even distribution of the electrostatic potential across the entire polyene. However, one has to point out that hCRBPII is missing any RSBH + counterion and our data demonstrate that the situation is clearly different in NeoR with low importance of the binding pocket and a main contribution of the active site.…”
Section: Resultsmentioning
confidence: 99%
“…30,[79][80][81][82] Another commonly used approach is the second-order approximate coupled cluster singles and doubles model (CC2). 32,83 It has been assessed specifically for excitation energies of organic molecules. 84 However, excitation energy calculations using the methods described above are computationally too demanding for the "Large" QM region (Figure 1), considering the computation of 3000 snapshots from thermal sampling.…”
Section: Assessment Of the Electronic Structure Methodsmentioning
confidence: 99%